Perceptions of placebo therapy among health practitioners in Jazan region of Saudi Arabia. - Hassan, Tabinda; Fauzi, Mahmood; Hasan, Deeba (International Journal of Health Sciences, 2011)
Background: Placebo therapy has always been a subject of controversy in the field of medicine. Some choose to admit it as "fake, irresponsible medicine" while others advocate its effectiveness in various clinical settings. With the advent of the recent concept of mind-body medicine, placebo has entered from fringe to mainstream therapeutics. Some clinicians use it for its actual positive outcomes while others use it merely to buy time until definitive diagnosis or even as a pacifier for patients. Objective: The present study was carried out to observe the perceptions about placebo therapy among health practitioners in Jazan region of Saudi Arabia Methodology: Data was analyzed through statistical analysis of retrospective questionnaires addressing various issues on placebo therapy, including types of placebo used in various clinical settings, mechanism of placebo action, ethics of use and openness with patients etc. Results: The study elucidated that the perceptions regarding placebo therapy are subjective and variable within and between institutions ranging from firm belief in its positive effects and efficacy; to neutral attitudes among some, to strong opposition for it among still others. Conclusion: More research is needed to ethically define the boundary between explicit fraudulence and marginalized evidence based therapeutic deception to effectively achieve the goal of positive health outcomes in patients. Key words: Placebo therapy, Saudi Arabia